Overview Of The Implementation Of Finger Grasping To Reduce Pain In Post Sectio Caesarea Patients At Rsud Prof Dr W. Z. Johannes Kupang - Maima, Qrenquar; Kapitan, Meiyeriance; Kleden, Simon Sani (Jurnal EduHealth, 2024)
Most post sectio caesarean mothers experience pain in the incision wound under the abdomen. One of the therapies that can be done to reduce pain in post cesarean section mothers is the finger grasp relaxation technique. The purpose of this study was to determine the description of the implementation of finger grasping to reduce pain in post sectio caesarea mothers at Prof. Dr. W. Z. Hospital Kupang. Johannes Kupang Hospital. This study used a qualitative approach with a type of case study research with a descriptive case study research design. The subjects of this study were two patients of post sectio caesarea mothers who were determined based on the inclusion and exclusion criteria. The pain measurement instrument used was a pain observation sheet (faces pain score / Wong baker faces scale). The results of the study obtained, before the implementation of finger grasping, Mrs. D's pain scale was severe pain (Value 7), and Mrs. M's pain scale was severe pain (Value 8). After implementing finger grasping for 3 consecutive days with a duration of 10-15 minutes every day, the results showed a decrease in the pain scale, in Mrs. D to a mild pain scale (Value 1), and the opposite in Mrs. M to a mild pain scale (Value 2). The conclusion of this study is that the implementation of finger grasping can reduce pain in post sectio caesarea maternal patients. It is hoped that patients and families can apply finger grasping relaxation techniques to reduce pain in post sectio caesarea maternal patients.